Dakwah Digital dan Hegemoni di Era Digital: Studi tentang Preferensi Politik Generasi Muslim melalui Media Sosial: A study of Muslim Generations’ Political Preferences by Social Media - Fatimah; Farid Pribadi (Journal of Southern Sociological Studies, 2025)
This study explores how digital da’wah influences the political preferences of Indonesia’s Muslim digital generation. Employing a qualitative case study approach, data were collected through in-depth interviews with Muslim university students aged 18–25 who actively consume religious content on platforms such as TikTok, YouTube, and Instagram. The findings reveal that digital preachers function as ideological agents who frame political choices as part of religious and moral obligations. The use of social media algorithms intensifies exposure to specific narratives, resulting in echo chambers that narrow perspectives and increase polarization. Using Antonio Gramsci’s theory of hegemony, the study highlights how ideological power is constructed and sustained through cultural consent and religious authority. However, the study also identifies critical audience responses that challenge dominant narratives, demonstrating that digital da’wah is not hegemonically total. This research underscores the importance of digital literacy and a more dialogical approach to online religious preaching as a way to foster healthy and inclusive political participation in the digital age.